2016
DOI: 10.2147/amep.s101099
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of teaching three common ear, nose, and throat conditions to medical students through video podcasts and written handouts: a pilot study

Abstract: BackgroundThis pilot study conducted at the Peninsula Medical School is one of very few studies to compare the use of video podcasts to traditional learning resources for medical students.MethodsWe developed written handouts and video podcasts for three common ear, nose, and throat conditions; epistaxis, otitis media, and tonsillitis. Forty-one second-year students were recruited via email. Students completed a 60-item true or false statement test written by the senior author (20 questions per subject). Studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
(12 reference statements)
1
11
0
Order By: Relevance
“…Moreover, students showed increased knowledge in the subject material at hand, as evaluated by pre-and post-lecture knowledge assessment [11,[13][14][15]17,19,21,22,24,25,27,[29][30][31][32]. Finally, multiple studies demonstrated that knowledge was equivalent (or better) between students learning through online lectures compared to traditional learning modalities, such as live didactic lectures [8,9,12,19,22,23,25,28,[33][34][35][36][37][38], with the exception of one study that found superior student knowledge acquisition from live lectures [39].…”
Section: Assessment Of Learning Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, students showed increased knowledge in the subject material at hand, as evaluated by pre-and post-lecture knowledge assessment [11,[13][14][15]17,19,21,22,24,25,27,[29][30][31][32]. Finally, multiple studies demonstrated that knowledge was equivalent (or better) between students learning through online lectures compared to traditional learning modalities, such as live didactic lectures [8,9,12,19,22,23,25,28,[33][34][35][36][37][38], with the exception of one study that found superior student knowledge acquisition from live lectures [39].…”
Section: Assessment Of Learning Outcomesmentioning
confidence: 99%
“…Regardless of the method of assessment, almost all studies reported high satisfaction and increased knowledge after intervention. Student self-assessment typically revealed positive attitudes toward online lectures as a teaching modality [7,8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Moreover, students showed increased knowledge in the subject material at hand, as evaluated by pre-and post-lecture knowledge assessment [11,[13][14][15]17,19,21,22,24,25,27,[29][30][31][32].…”
Section: Assessment Of Learning Outcomesmentioning
confidence: 99%
“…One study suggests that podcasts in conjunction with quizzes improve knowledge retention compared to traditional live lectures. 3 A study from Plymouth, UK compared the use of podcasts with more traditional handouts in self-directed education across three common ear, nose, and throat (ENT) conditions namely epistaxis, otitis media, and tonsillitis. 3 The authors developed written handouts and video podcasts for these conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 3 A study from Plymouth, UK compared the use of podcasts with more traditional handouts in self-directed education across three common ear, nose, and throat (ENT) conditions namely epistaxis, otitis media, and tonsillitis. 3 The authors developed written handouts and video podcasts for these conditions. Participating students were assessed by multiple choice questions (MCQ) test as a base line and 1 month after the intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation